(untitled) (INNOVATIVE ECONOMY, 2024)
Zastavnyi A.R., Homotiuk A.О., Uhryn B.V. CIVILIZATIONAL PRECONDITIONS OF FINANCIAL INTEGRATION IN THE MIDDLE EAST AND GLOBAL CHALLENGES FOR ISLAMIC FINANCE Purpose. The aim of the article is to assess the main trends of financial integration in the Middle East, shaped by civilizational factors, and to identify the peculiarities of Islamic finance development in the context of global challenges. Methodology of research. The following general scientific and special research methods were used to achieve the set goal: analysis and synthesis, historical-logical – for formulating theoretical generalizations and conclusions; system analysis method; methods of induction and deduction; comparison method – for identifying the peculiarities of integration processes in the Middle East; method of graphical visualization to display trends and dynamics of financial integration. Findings. It is argued that regional integration processes do not contradict globalization processes, but significant differences are observed between regions. It is substantiated that the issue of economic integration requires the development of innovative approaches to its understanding, including through the growing role of civilizational factors in these processes. The article confirms the multidimensionality of financial integration issues, including through the integration of financial markets. The peculiarities of financial integration in the Middle East are revealed, where identity is preserved and new technologies are introduced. The institutional provision of financial integration in the region is considered, and different degrees of involvement of countries in the region in integration processes are identified. The principles of Islamic finance are analysed and their role in the development of financial integration is confirmed. The stability of Islamic finance during crises and their social orientation are substantiated. An assessment of the investment component of financial integration is carried out. The role of fintech in the development of the region is identified, and the main challenges for financial integration are determined. Originality. Approaches to the systematic analysis of the civilizational prerequisites for the formation of financial integration in the Middle East have gained further development, the main innovative trends for the region regarding the institutional basis of financial integration and the introduction of new financial technologies were identified, which allowed to formulate the peculiarities of Islamic finance development in the region, which, along with internal challenges, feels the impact of global ones. Practical value. The conclusions, recommendations and substantiated results of research can be used in the development of strategic directions of partnership with Middle Eastern countries, borrowing the experience of countries in the region regarding the introduction of Islamic financial model tools. Key words: Middle East, civilizational preconditions of development, global challenges, foreign investments, regional economic integration, sustainable development, financial integration, financial markets, financial technologies.